Apparent Diffusion Coefficients for Differentiation of Cerebellar Tumors in Children - Rumboldt, Z.; Camacho, D.L.A.; Lake, D.; Welsh, C.T.; Castillo, M. (American Journal of Neuroradiology, 2006)
BACKGROUND AND PURPOSE: Diffusion-weighted imaging (DWI) and apparent diffusion coefficient (ADC) maps provide information at MR imaging that may reflect cell attenuation and integrity. We hypothesized that cerebellar tumors in children can be differentiated by their ADC values.METHODS: Brain MR imaging studies that included ADC maps were retrospectively reviewed in 32 patients with histologically proved cerebellar neoplasm. There were 17 juvenile pilocytic astrocytomas (JPA), 8 medulloblastomas, 5 ependymomas, and 2 rhabdoid (atypical teratoid/rhabdoid tumor [AT/RT]) tumors. Absolute ADC values of contrast-enhancing solid tumor regions and ADC ratios (ADC of solid tumor to ADC of normal-appearing white matter) were compared with the histologic diagnosis. ADC values and ratios of JPAs, medulloblastomas, and ependymomas were compared by using a 2-tailed t test and one-way analysis of variance (ANOVA).RESULTS: ADC values were significantly higher in pilocytic astrocytomas (1.65 ± 0.27) (mean ± SD) than in ependymomas (1.10 ± 0.11) (P = .0003) and medulloblastomas (0.66 ± 0.15) (P < .0001). Ependymomas demonstrated significantly higher ADC values than medulloblastomas (P = .0005). The observed differences were statistically significant on ANOVA (P < .001). ADC ratios were also significantly different among these 3 tumor types. AT/RT ADC values were similar to medulloblastoma. The range of ADC values and ratios within JPAs and ependymomas did not overlap with that of medulloblastomas.CONCLUSION: Assessment of ADC values of enhancing solid tumor is a simple and reliable technique for preoperative differentiation of cerebellar tumors in pediatric patients. Our cutoff values of >1.4 × 103 mm2/s for JPA and <0.9 × 103 mm2/s for medulloblastoma were 100% specific.